0840 Be Wary Of Adjustment Disorder with Anxiety In Patient With Insomnia And Discomfort With Positive Pressure Airway Therapy. (25th May 2022) - Jamil, Saad Bin; Kachechian, Talar; Doghramji, Karl; Fast, Zhanna
Abstract: Introduction: Insomnia is a common complaint. When it occurs in the context of treatment with continuous positive airway pressure (CPAP), it can complicate treatment and lead to dissatisfaction with CPAP therapy. Adjustment disorder with anxiety (ADWA) is a condition that develops following an identifiable stressor and can be associated with insomnia. We describe a case of ADWA causing disrupted sleep and dissatisfaction with CPAP therapy. Report of Cases: The patient is an 80-year-old man with history of severe obstructive sleep apnea (OSA) and chronic obstructive lung disease, under stable management with CPAP. During a routine follow up visit, he reported the recent onset of frequent, and often prolonged, nocturnal awakenings associated with daytime sleepiness and fatigue. Insomnia was associated with discomfort with breathing, especially during exhalation, while using CPAP. His machine report indicated a significant decrement in compliance. Upon questioning, he reported that a few of his family members had died unexpectedly, following which he began to experience significant anxiety. His wife noted that he had become moody and irritable. On examination, the patient was visibly anxious; his speech was accelerated and animated, and he displayed psychomotor activation. Affect also displayed despondency. The patient was diagnosed with ADWA leading to insomnia and discomfort with CPAP use. He was prescribed buspirone 10 mg twice daily. On two week follow up patient reported no improvement in symptoms and was switched to escitalopram 10 mg daily. Following approximately three weeks, his clinical evaluation revealed significant improvement in mood; anxiety had dissipated, and sleep was more continuous with infrequent and brief awakenings. Daytime alertness had been restored. Of interest was the temporary return of anxiety and insomnia symptoms following the brief discontinuation of escitalopram because of hospitalization. Conclusion: ADWA can occur in the setting of recent stressors and can result in sudden onset of insomnia, compromise CPAP adherence and decrease subjective benefit from PAP therapy. This case highlights the importance of questioning patients for the possibility of recent stressors and traumatic events when they develop difficulties with PAP use. These may indicate the presence of ADWA, whose management can restore CPAP compliance and improve sleep quality and daytime functioning. Support (If Any):